A reestruturação organizacional do modelo de saúde e o processo de educação permanente no SUS - Borges, Josefa Lusitânia de Jesus (2009)
Headed by the Sanitary Movement, Brazilian Public Health Services undergone a comprehensive organizational, managerial and streamlined restructuring with political dimensions. This study aims at examining the training process developed at CEPS Center of Continuing Education in Health in Aracuju, State of Sergipe addressing the relation among Education, Work and Health under a historical perspective and global overview in compliance with the guiding principles of the Ministry of Health Management Policy of Work and Education. The object hereof includes the experiences of nurses participating in this training process, which was developed from 2002 to 2006 grounded on the restructuring of the organizational model of health and qualification policy. The qualitative approach using case study allowed the consulting of various sources such as: literature, documents, management reports, political and pedagogical project of Expertise Integrated in Public Health EISC , and the implementation of seventeen semi-structured interviews with the nurses who participated in the EISC. Special attention was given to the teaching of the exposure factor, used in the CEPS, meaning a way of seeing and intervening a real and coherent pedagogical possibility for the exercise of a critical educational reality-related policy envisaging the transformation of the actual practices based on the contents worked upon. The data reveal the challenges faced by the workers, students and nurses in assuming with independence the conduction of the learning process. To the work in health, they value the relational skills, behavioral and accountability related to the technical-instrumental skills, related to scientific knowledge. By means of reception, dynamic health system employed in the local health system of Aracaju, the introduction of soft technologies brought about impacts in the nurses´ working process.The use of teaching/learning methodologies is hereby recommended in order to form questioning individuals, able to solve problems, and as well as to take stand and be responsible, interacting and dialoguing with each other.